A Decade of GRB Follow-Up by BOOTES in Spain (2003–2013) - Martin Jelínek; Alberto J. Castro-Tirado; Ronan Cunniffe; Javier Gorosabel; Stanislav Vítek; Petr Kubánek; Antonio de Ugarte Postigo; Sergey Guziy; Juan C. Tello; Petr Páta; Rubén Sánchez-Ramírez; Samantha Oates; et al. (Advances in Astronomy)
This article covers ten years of GRB follow-ups by the Spanish BOOTES stations: 71 follow-ups providing 23 detections. Follow-ups by BOOTES-1B from 2005 to 2008 were given in a previous article and are here reviewed and updated, and additional detection data points are included as the former article merely stated their existence. The all-sky cameras CASSANDRA have not yet detected any GRB optical afterglows, but limits are reported where available.